Characterization of the Protective HIV-1 CTL Epitopes and the Corresponding HLA Class I Alleles: A Step towards Designing CTL Based HIV-1 Vaccine. (18th March 2014) - Chakraborty, Sajib; Rahman, Taibur; Chakravorty, Rajib
Abstract : Human immunodeficiency virus (HIV) possesses a major threat to the human life largely due to the unavailability of an efficacious vaccine and poor access to the antiretroviral drugs against this deadly virus. High mutation rate in the viral genome underlying the antigenic variability of the viral proteome is the major hindrance as far as the antibody based vaccine development is concerned. Although the exact mechanism by which CTL epitopes and the restricting HLA alleles mediate their action towards slow disease progression is still not clear, the important CTL restricted epitopes for controlling viral infections can be utilized in future vaccine design. This study was designed for the characterization the HIV-1 optimal CTL epitopes and their corresponding HLA alleles. CTL epitope cluster distribution analysis revealed only two HIV-1 proteins, namely, Nef and Gag, which have significant cluster forming capacity. We have found the role of specific HLA supertypes such as HLA B*07, HLA B*58, and HLA A*03 in selecting the hydrophobic and conserved amino acid positions within Nef and Gag proteins, to be presented as epitopes. The analyses revealed that the clusters of optimal epitopes for Nef and p24 proteins of HIV-1 could potentially serve as a source of vaccine.